Culture and commitment as antecedents of performance in the food and beverage sector - Oliveira, Paulo Sergio Gonçalves de; Mathias, Bruno Santana; Wada, Elizabeth Kyoko; Silva, Luciano Ferreira da (Revista de Administração da UFSM, 2024)
Purpose: The objective of the article is to verify the influence of antecedents such as culture and commitment on restaurant organisational performance and assess how they can impact managerial practices. This would explain the relationship between the exogenous variables of the model, thus providing managers with a parameter for managing the dimensions of culture, commitment, and performance. Design/methodology/approach: Data were analysed using structural equation analysis (PLS-PM) and collected through a questionnaire with 45 assertions over a period of 2 months, obtaining 116 valid answers. Findings: Four hypotheses were supported: H1—Innovative culture positively influences the affective commitment of restaurant employees (Γ=0.466); H8—Supportive culture influences normative commitment (Γ=0.270); H9—Supportive culture influences continuance commitment (Γ=0.293); and H10—Affective commitment positively influences bar and restaurant performance (Γ=0.293). Managerial contributions: The model developed for this study can be used by restaurant managers to manage their employees and improve their organisational performance. Practical implications: This model’s practical implications were that it could be used to guide restaurant decisions toward performance improvement. Originality/value: The study fills a gap by proposing a managerial model that considers aspects of people management, such as culture and staff engagement, to improve the organisational performance of bars and restaurants.